ANALISIS BUTIR SOAL ISMUBA (AL-ISLAM KEMUHAMMADIYAHAN DAN BAHASA ARAB) KELAS IV SD MUHAMMADIYAH 5 JAKARTA SELATAN - Lismawati, Lismawati; Fahmi, Ari Khairurrijal (Universitas Muhammadiyah Prof Dr Hamka, 2019)
Learning ISMUBA (al-Islam, Kemuhammadiyahan and Arabic) is the hallmark of an Education Institution in all Muhammadiyah schools. An institution that holds realization of learning al-Islam, Kemuhammadiyahan and Arabic language is SD Muhammadiyah 5 South Jakarta is one of the Muhammadiyah elementary school located in Jalan Limau Kebayoran Baru South Jakarta. The type of this research is descriptive quantitative with qualitative descriptive interpretation. Place conducted research In SD Muhammadiyah 5 Jakarta Selatan While the time of research from September to Novermber 2017. Population research is all students In SD Muhammadiyah 5 South Jakarta class IV. Sample used in this research is saturated population that is all student of Class IV. The data collected includes primary data. Primary data obtained from the answer sheet of students of SD Muhammadiyah 5 Jakarta Selatan on the subjects of alIslam, Kemuhammadiyahan and Arabic. Analysis of items by using IRT (Item Response Theory) by using item software to see the level of difficulty problem, distinguishing power. The results obtained from the ITEMAN application will be interpreted in accordance with the provisions of different problem power and problem level.